The Patient Perspective on Radiogenomics Testing for Breast Radiation Toxicity. Issue 3 (March 2018) - Rattay, T.; Symonds, R.P.; Shokuhi, S.; Talbot, C.J.; Schnur, J.B.
Abstract: Aims: In the field of radiogenomics, several potential predictive genetic markers have been identified that are associated with individual susceptibility to radiation toxicity. Predictive models of radiation toxicity incorporating radiogenomics and other biomarkers are being developed as part of the ongoing multicentre REQUITE trial. The purpose of this study was to explore patient attitudes towards future predictive radiogenomics testing for breast radiation toxicity. Patients and methods: Twenty-one semi-structured interviews were conducted with breast cancer patients taking part in the REQUITE study at one centre. We used inductive thematic analysis to generate common themes. Results: We identified three emerging themes describing attitudes and feelings towards a predictive radiogenomics test for breast radiation toxicity: theme 1 – willingness to undergo a test (subthemes – information, trusted expert); theme 2 – implications of a test (subthemes – preparation and planning, anxiety without recourse); theme 3 – impact on treatment decision-making (subthemes – prioritising cancer cure, preserving breast integrity, patient preferences). Conclusions: Results from the present study indicate that patients support and have confidence in the validity of a radiogenomics test for breast radiation toxicity, but they would prefer the result be provided to healthcare professionals. Except in cases of significant chronic symptoms and pain or significant end-organ damage, participants in this study rarely felt that advance knowledge of their personal risk of breast radiation toxicity would influence their treatment decision-making. These findings provide a number of insights that will allow us to anticipate how patients are likely to engage with predictive radiogenomics testing in the future. Highlights: Patients' views and opinions on predictive radiogenomics testing were investigated. Semi-structured interviews with breast cancer patients enrolled in the prospective REQUITE cohort. Participants would prefer the test result to be provided to healthcare professionals rather than directly to patients. Participants rarely felt that advance knowledge of their risk of radiation toxicity would influence their treatment decision. Participants were prepared to consider a treatment change, if predicted to have significant chronic side-effects or end-organ damage.